Collective Farming Groups in Kerala-Aspirations and Challenges - Mridula N. (Journal of Community Mobilization and Sustainable Development, 2018)
The study was conducted at a time when the vegetables and fruits imported to Kerala were showing high quantities of toxic pesticides which were detrimental to human health. As a part of producing cleaner, safer vegetables and fruits many local food production communities had taken up organic cultivation. The study brings out the aspirations and challenges of such collective farming units in achieving their target of increased production of ‘safe to eat’ foods. The aspirations indicate the type of financial and technical support needed by these units. Their challenges need immediate attention by the government and policy makers so that their problems get solutions or better alternatives, which would lead to a greener and healthier agriculture scenario in Kerala.